LIABILITY OF TRUST SERVICE PROVIDERS - SELECTED ASPECTS - Jóźwiak, Id (Człowiek w cyberprzestrzeni, 2020)
The regulation of trust services and electronic identification means in the European Union responds to the growing demand for covering such issues as confirming the identity of the party performing the legal transaction by electronic means and the time of performing the action or ensuring the integrity of the content of submitted declarations of intent. Nonetheless, amidst rapid technological progress coupled with a growing threat of cybercrime, the security of electronic legal transactions may not be fully guaranteed. Whereas the use of electronic services requires the use of appropriate software, which can be remotely accessed by a supplier or unauthorized person carrying out a hacking attack, a question arises about the liability of providers software and hardware enabling the use of trust services for their security, that is the liability of trust service providers. This paper presents selected aspects of this issue, crucial from the point of view of security of users and recipients of trust services.